Social-occupational impact and level of satisfaction in patients included in a remote monitoring pacemaker programme. (14th October 2021) - Perez Diaz, P; Bastante Diaz, M C; Campos Perez De Madrid, E; Fernandez Trujillo, A; Cano Rosado, L; Jimenez Diaz, J; Higuera Sobrino, F; Bermejo Calvillo, N; Casas De Miguel, A M; ,
Abstract: Background: When patients fitted with pacemakers have to attend arrhythmia appointments, this often reduces their independence and involves their caregivers having to take time off work, along with an increase in spending on healthcare transport. Purpose: We describe the impact of remote monitoring of pacemaker implemented by our Arrhythmia Unit in our patient's live and the reduction in social, occupational and financial impact on these patients. Methods: Prospective observational study including 160 patients on the remote monitoring pacemaker programme between January 2016 and January 2017. We handed a satisfaction survey to these patients after the face-to-face monitoring appointment, which analysed variables such as waiting time, attention and treatment received, need for accompaniment of a relative, method of travel and kilometres travelled, level of satisfaction with the remote monitoring system, proposals for improvement, etc. Results: The patients spent a median of 60±30 minutes on the remote monitoring, with a distance travelled of 1.4±4.9 km, rating their level of satisfaction at the remote monitoring as excellent (35%), good (61%) and average (3%) (Figure 1). In the face-to-face appointment, most of them were accompanied (86%) and arrived by private car (66%), with 54% of family members needing to take time off work. 19.4% of patients arrived by ambulance and 8.8% by bus. The median time spent was 150±120 minutes, and the distance travelled was 63±105 km. Conclusions: The remote monitoring pacemaker programme in our health district has a very positive healthcare and social-occupational impact, which is manifested both from an objective point of view (greater independence, less time spent per appointment, less distance travelled, fewer healthcare transport needs and less workplace absenteeism by family members, etc.) and a subjective point of view (lower impact of appointments on patients' lives and greater perception of satisfaction from the patients and their companions). Funding Acknowledgement: Type of funding sources: None.